Profile of poisoning in children and adolescents at a tertiary care centre - S. A., Ravikumar; K., Arivoli; P., Parameshwari; R. V., Dhakshayani; R., Jayanthi; S., Sara; Durai, Latha (International Journal of Contemporary Pediatrics, 2025)
Background: This study examines exogenous poisoning-related hospitalizations among children and adolescents at Chengalpattu medical college hospital. It aims to identify risk factors for unintentional poisoning in individuals aged 1-18 and assess clinical outcomes. Additionally, it seeks to characterize the types and outcomes of poisonings in this demographic. Methods: A retrospective analysis was conducted using medical records of all admissions with confirmed poisoning diagnoses from January 1, 2022, to December 31, 2022, at Chengalpattu medical college hospital. Patients aged 1 to 18 years were included. Cases involving food poisoning, adverse drug reactions, and animal-related envenomation were excluded. Data collected included demographic details, type of poisoning, time to hospitalization, treatment given, and outcomes. Results: Out of 2,123 total poisoning cases, 389 (18.3%) involved patients under 18 years. A majority were female (58.4%), with a mean age of 11.61 years. Most cases (64%) originated from rural areas. The leading agents were corrosives (52.5%), organophosphorus compounds (14.1%), and oleander (13.6%). Corrosive poisoning was predominant among children under five, indicating accidental ingestion. The median time to hospital admission was 3.29 hours, and the Glasgow coma scale score was 12.83. Medical management was successful in 98.9% of cases, while the overall mortality rate was 1%, with organophosphorus poisoning being the most fatal. Conclusions: Preventive strategies and public education are essential, especially in rural areas, to reduce poisoning incidents. The study also highlights the growing concern of intentional poisonings and underlines the importance of mental health support for adolescents, particularly girls.